The effect of water supply for yield formation of processing tomato - Helyes, Lajos; Pék, Zoltán (Acta Agraria Debreceniensis, 2012)
The effect of irrigation on tomato yield depends on the actual weather conditions, basically the air temperature and precipitation (quantity and dispersion). The irrigated plants gave a significantly higher yield, and rainfed plants showed a yield loss. The optimum water supply treatment gave a significantly higher proportion of lycopene than the control (rainfed) treatment (89% and 80% respectively) in case of Brixsol F1 variety. In spite of this we have not found significant difference in case of Strombolino F1 (cherry type). Content of total poly-phenols measured in Strombolino F1 (cherry type) was significantly higher than that found in the Brixol F1 (normal type). The optimum water supply treatment resulted in a significantly lower content of total polyphenols in both years. Tomato fruits are rich in polyphenols the largest amount of which is rutin from among the identified components.